2020
DOI: 10.1212/wnl.0000000000010669
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neuroplasticity of the white matter connectome in children with perinatal stroke

Abstract: ObjectiveWe aimed to employ diffusion imaging connectome methods to explore network development in the contralesional hemisphere of children with perinatal stroke and its relationship to clinical function. We hypothesized alterations in global efficiency of the intact hemisphere would correlate with clinical disability.MethodsChildren with unilateral perinatal arterial (n = 26) or venous (n = 27) stroke and typically developing controls (n = 32) underwent 3T diffusion and T1 anatomical MRI and completed establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 46 publications
8
26
0
Order By: Relevance
“…We have recently confirmed that a structural connectomics approach is feasible in perinatal stroke. 144 When investigating the non-lesioned hemisphere, we revealed modest but consistent relationships between baseline clinical motor function and some graph theory metrics. 144 Advanced diffusion imaging methods may therefore open the door for investigating how structural and whole-brain connectivity change following intensive occupational therapy or noninvasive brain stimulation.…”
Section: Diffusion Imagingmentioning
confidence: 72%
See 1 more Smart Citation
“…We have recently confirmed that a structural connectomics approach is feasible in perinatal stroke. 144 When investigating the non-lesioned hemisphere, we revealed modest but consistent relationships between baseline clinical motor function and some graph theory metrics. 144 Advanced diffusion imaging methods may therefore open the door for investigating how structural and whole-brain connectivity change following intensive occupational therapy or noninvasive brain stimulation.…”
Section: Diffusion Imagingmentioning
confidence: 72%
“…144 When investigating the non-lesioned hemisphere, we revealed modest but consistent relationships between baseline clinical motor function and some graph theory metrics. 144 Advanced diffusion imaging methods may therefore open the door for investigating how structural and whole-brain connectivity change following intensive occupational therapy or noninvasive brain stimulation. Baseline microstructural variables in the lesioned CST correlated with larger gains in rehabilitation in children with unilateral cerebral palsy 145 though results vary.…”
Section: Diffusion Imagingmentioning
confidence: 72%
“…Previous studies have found that structural connections between motor-related brain regions play an important role in movement development ( Craig et al, 2020 ). Only 32 of A-LF infants and 17 of NA-HF infants had qualified MRI examination.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical neuroimaging research on early motor abilities is still limited. Previous studies have found that structural connections between motor-related brain regions play an important role in movement development ( Craig et al, 2020 ). Cranial magnetic resonance (MRI) is a common and valuable method to study the infant brain functions, and diffusion tensor imaging (DTI) is a non-invasive method to study the white matter of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others have demonstrated the ability of tractography to better understand sensory and motor functions in children with perinatal stroke (Hodge et al, 2017;Kuczynski et al, 2017;Kuczynski et al, 2018;van der Aa et al, 2011). Furthermore, recent evidence has emphasized the essential role of widespread network alterations in the nonlesioned hemisphere in determining perinatal stroke outcomes (Craig et al, 2020), emphasizing the importance of interhemispheric connectivity.…”
mentioning
confidence: 89%